Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13063-019-4010-3
|View full text |Cite
|
Sign up to set email alerts
|

Letter on: “An analysis of deficiencies in the data of interventional drug trials registered with Clinical Trials Registry – India”

Abstract: An article published in this journal analyses the deficiencies in the data of interventional drug trials registered with Clinical Trials Registry-India. We wish to rebut some of the inferences and highlight the pitfalls of a purely automated analysis of registry data as posited by the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Apart from India and USA, there are many countries which maintain their own clinical trial registries including European Union, Japan, China, Korea, Australia, Brazil, Germany, Thailand, and Sri Lanka. [ 11 ] The present study was planned to analyze and evaluate the compliance of Indian and global sponsors with the Clinical Trials Registry-India (CTRI) in terms of reporting of clinical trial results and to compare the proportion of reporting of results with the US FDA Clinical Trial Registry called Clinical Trials. gov website.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from India and USA, there are many countries which maintain their own clinical trial registries including European Union, Japan, China, Korea, Australia, Brazil, Germany, Thailand, and Sri Lanka. [ 11 ] The present study was planned to analyze and evaluate the compliance of Indian and global sponsors with the Clinical Trials Registry-India (CTRI) in terms of reporting of clinical trial results and to compare the proportion of reporting of results with the US FDA Clinical Trial Registry called Clinical Trials. gov website.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] However, most of these deficiencies were addressed in the Letter to the Editor to the same journal by Maulik et al . [ 11 ] In this audit, we aimed to evaluate only the clinical trial results field of CTRI and looked for compliance of Indian and global sponsors with clinical trial site in India in terms of reporting of clinical trial results. We also wished to compare the proportion of studies that reported clinical trial results at CTRI with that of published data available at the US FDA Clinical Trial Registry called as Clinical Trials.gov maintained by the U. S. National Library of Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…We first consider the listing of more ECs than sites. The CTRI staff have explained one possible cause of this [29], as follows. If new sites are to be added to the CTRI record, the trialist first uploads the ethics approval documents.…”
Section: Plos Global Public Healthmentioning
confidence: 99%